SOSIALISASI PENGGUNAAN QRIS UNTUK TRANSAKSI DIGITAL MASYARAKAT DI KOTA WAMENA KABUPATEN JAYAWIJAYA - Difinubun, Muhamad Fagi; Wibowo, Didik Usman; Medlama, Mepa (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2024)
The Qris payment method is a modification of the previous cash payment to cashless, this emerged after the COVID-19 pandemic outbreak, one of the impacts of which was through money. Payment for the QRIS method is made by Scanning Barcodes using a mobile application. In the city of Wamena, access to service infrastructure is still very minimal. Poor internet connectivity and network quality in Wamena City greatly affect the use of Qris. However, since 2023, some people have started to switch to using this method to shop in stores. This outreach was carried out by taking several non-probability and probability samples which were then analyzed using descriptive quantitative methods with the hope of providing information to the public about the benefits and procedures for using QRIS which will greatly help people in shopping for daily needs Keywords: Digital Payment, Society, QRIS